TRACE ELEMENT PARTITIONING IN PLAGIOCLASE FELDSPAR - Bedard J.H. (My University, 2006)
Compilation and interpretation of experimental and natural Nernst partition coefficient (plagioclase/meltD) data show that, with a few exceptions, increases in plagioclase/meltD correlate with decreasing anorthite-content of plagioclase. In contrast, increases of plagioclase/meltD for Ga, Sc, Cu, Zn, Zr, Hf and Ti, are better correlated against decreasing melt MgO or increasing melt SiO2 contents. plagioclase/meltD for Ti and the rare earth elements (REE) show little dependence on temperature, but increase as the melt water content increases. plagioclase/meltD for K and Sr are sensitive to pressure. Variations of D0 (the strain compensated partition coefficient), r0 (the size of the site into which REE substitute), and E (Young’s Modulus of this site) were parameterized against variations of melt SiO2, the An-content of plagioclase, and other combinations of variables, allowing plagioclase/meltDREE-Y to be calculated from a variety of input parameters. The interrelations of temperature, melt MgO and SiO2 content, and plagioclase anorthite-content for wet and dry systems were also parameterized to facilitate interpolation where such data are lacking. When combined, these semi-empirical parameterizations yield plagioclase/meltD results comparable to available experimental and natural data. Crown Copyright ? 2006.
Keywords: EXPERIMENTAL MINERALOGY; PARTITIONING; PLAGIOCLASE; TRACE ELEMENT